Effects of early estradiol valerate administration on bone turnover markers in surgically induced menopausal women - Jarika Vatrasresth; Ammarin Suwan; Krasean Panyakhamlerd (BMC, 2021)
Abstract Background Compared with a natural process, surgically induced menopausal women have a higher bone loss rate. This study aims to evaluate early treatment with estradiol valerate on bone turnover markers after surgically induced menopause. Methods This prospective study included 41 pre and perimenopausal women who underwent hysterectomy with oophorectomy for benign gynecologic conditions. Two weeks after the operation, all participants were assessed for menopausal hormone therapy (MHT) indications. Estrogen therapy was prescribed for those who had indications and accepted treatment (hormone treatment group). The others who had no MHT indication were allocated to the no-treatment group. Serum CTX and P1NP levels at preoperative and 12 weeks postoperative were measured and set as the primary outcome. Within the same group, serum CTX and P1NP before and after surgical menopause were analyzed using Wilcoxon signed-rank test. ANCOVA was used to compare serum CTX and P1NP at 12 weeks after surgical menopause between the two groups. Spearman's rank correlation coefficient analysis analyzed the correlation between age and baseline bone turnover markers. A p-value of < 0.05 was considered statistically significant. Results At 12 weeks after surgery, there were no significant differences in serum CTX and P1NP levels in the hormone treatment group compared to baseline. In contrast, serum CTX and P1NP levels were significantly elevated among women who did not receive hormone treatment (p-value < 0.001 and 0.002, respectively). Serum CTX and P1NP at 12 weeks were significantly different between the two groups (p-value < 0.001 and 0.004, respectively). Conclusion Early estrogen administration with oral estradiol valerate could significantly suppress the high bone remodeling in surgically induced menopausal women. Trial registration Thai Clinical Trial Registry identification number TCTR20190808004, retrospective registered since 2019-08-08. http://www.thaiclinicaltrials.org/show/TCTR20190808004 .